Climate Change Will Lead to a Significant Reduction in the Global Cultivation of Panicum milliaceum - Pan Jiang; Junyi Jiang; Cong Yang; Xinchen Gu; Yi Huang; Liang Liu (Atmosphere, 2023)
Panicum milliaceum is a specialty crop that maintains the economic stability of agriculture in arid and barren regions of the world. Predicting the potential geographic distribution of Panicum milliaceum globally and clarifying the ecological needs of Panicum milliaceum will help to advance the development of agriculture, which is important for the maintenance of human life and health. In this study, based on 5637 global distribution records of Panicum milliaceum, we used the MaxEnt model and ArcGIS software, the Beijing Climate Center Climate System Model (BCC-CSM2-MR) was selected to predict the potential global geographic distribution of Panicum milliaceum in the present and future in combination with the environmental factor variables; we evaluated the significant factors constraining the potential geographic distribution of Panicum milliaceum by combining the contributions of environmental factor variables; and we assessed the accuracy of the MaxEnt model by using AUC values and Kappa statistics. The results showed that the MaxEnt model was highly accurate, the simulation results were credible, and the total suitable area of Panicum milliaceum in the world is 4563.82 × 104 km2. The high habitat area of Panicum milliaceum is 484.95 × 104 km2, accounting for 10.63% of the total habitat area, and is mainly distributed in the United States, the Russian Federation, France, Ukraine, Australia, Germany, etc. The soil factor (hswd) was the most important environmental factor limiting the potential geographic distribution of Panicum milliaceum, followed by the precipitation factor (Precipitation of the Driest Month, bio14) and temperature factor (Mean Temperature of the Wettest Quarter, bio8). Under four future climate change scenarios, the area of the potential geographic distribution of Panicum milliaceum decreased to different extents at different levels compared to the contemporary period. Therefore, climate change may significantly affect the global distribution pattern of Panicum milliaceum cultivation in the future and thus reshape global Panicum milliaceum production and trade patterns.